Conceptualizing issues relating to the bills of quantities - Bandi, Shamsul Hadi; Abdullah, Fadhlin (2012)
Bills of Quantities (BQ) are an indispensable tool for the management of a construction project. In recent years, numerous studies have been conducted to assess its applicability and many without doubt have recognized its significance in the construction process. Despite this recognition, reviews of the literatures have suggested that the BQ is flagged with issues which rendered it to be less useful to certain parties in construction. Empirical evidence from past researches have justified the presence of the issues, however without any coordinated effort in drawing the desired solution, the issues remain daunting and continue to become an academic and industry-wide concern. In view of the above, this paper seeks to critically identify and classify all issues related to the BQ with an aim to propose a conceptual framework as a basis to understand BQ related issues in a holistic manner. The paper which employed an extensive, broad based literature review approach had established that issues related to the inadequacy of BQ information as significant across the literatures thus prompting for action to be carried out. As an approach to understand the significant issue further, the paper has proposed the conceptual framework which contains what supposed to be the ideal situation as opposed to the current situation and further called for the establishment of the line of information equilibrium as the basis for assessing the issue. With such a framework in place, it is envisaged that the issue concerning BQ information imbalance could be untangled to achieve the desired solution.